(untitled) (Bangladesh Agronomy Journal, 2021)
Four wheat variety/genotype (BARI Gom-26, BAW-1202, BAW-1182 and BARI Gom-27) were tested under three heat stress regimes (normal, moderate and severe) to evaluate the effect of late seeding warmer condition on phenology and yield of wheat, as well as to identify suitable cultivars to develop heat-tolerant genotypes at Hajee Mohammad Danesh Science and Technology University (HSTU), Dinajpur during November, 2016 to April, 2017. Results revealed that genotype BAW-1182 and BAW-1202 showed greater thermostability of cell membrane with acceptable yield performance under heat stress condition. The order of tolerance based on heat susceptibility index (based on grain yield) was BAW-1182>BAW-1202>BARI Gom-27>BARI Gom-26 under heat stress conditions. Thus, BAW-1182 and BAW-1202 have the greatest potential to be used as high-yielding wheat genotypes under warm to hot environments and could be used in a breeding programme to develop heat-tolerant wheat. Bangladesh Agron. J. 2021, 24(1): 13-23